2019
DOI: 10.1177/0013164419826237
|View full text |Cite
|
Sign up to set email alerts
|

Making Inferences About Teacher Observation Scores Over Time

Abstract: Observation protocol scores are commonly used as status measures to support inferences about teacher practices. When multiple observations are collected for the same teacher over the course of a year, some portion of a teacher’s score on each occasion may be attributable to the rater, lesson, and the time of year of the observation. All three of these are facets that can threaten the generalizability of teacher scores, but the role of time is easiest to overlook. A generalizability theory framework is used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…While nominally class-to-class variation is to be expected, here it is considered error given that we are attempting to generalize what we see in a few class sessions to a whole course term. As noted, this is a common practice in other Gstudies that examine the number of occasions classes have been observed (Briggs & Alzen, 2019;Hill et al, 2012). Some researchers also call these differentiation and instrumentation sources of variance corresponding to true and error variance (Cardinet et al, 2011).…”
Section: G-studies and Decision Studies (D-studies)mentioning
confidence: 95%
“…While nominally class-to-class variation is to be expected, here it is considered error given that we are attempting to generalize what we see in a few class sessions to a whole course term. As noted, this is a common practice in other Gstudies that examine the number of occasions classes have been observed (Briggs & Alzen, 2019;Hill et al, 2012). Some researchers also call these differentiation and instrumentation sources of variance corresponding to true and error variance (Cardinet et al, 2011).…”
Section: G-studies and Decision Studies (D-studies)mentioning
confidence: 95%
“…Since its introduction in Cronbach et al (1972), G theory has emerged as one of the more frequently used modern test theories. Applications of G theory have extended into many scientific fields, including behavioral and social sciences (e.g., see Arterberry et al, 2014;Bergeron et al, 2008;Brennan & Liao, 2020;Briggs & Alzen, 2019;Christ et al, 2010;Clauser et al, 2020;Halvorsen et al, 2006;Lakes & Hoyt, 2009;Lee & Lewis, 2008;Lei et al, 2007;Shavelson et al, 1993;Vispoel et al, 2018;Wasserman et al, 2008). In addition, G theory has been linked to other techniques, such as structural equation modeling (see Ark, 2015, andVispoel et al, 2018).…”
Section: Some Advanced Issuesmentioning
confidence: 99%
“…First, observer ratings are inherently subjective as observers may bring their own biases, beliefs, interpretation of teaching behaviors to the rating process, causing potential variability in ratings and negatively impact the reliability and validity of such ratings (Praetorius et al, 2014). Because of this, observers need to be rigorously trained on the observation tool or rubric, and then subsequently calibrated to ensure that they are applying the tool or rubric consistently from the beginning to the end (Briggs & Alzen, 2019). Additionally, observers are typically only able to observe a limited portion of a teacher's practice and may not have a complete understanding of the context in which teaching is occurring; such limited scope may also negatively impact the validity and reliability of the ratings (Weston et al, 2021).…”
Section: Observer Rated Instructional Practicesmentioning
confidence: 99%
“…Despite these limitations, observer-rated instructional quality has remained a valuable tool. Obviously, its validity and reliability largely rely on that of the observation tool or rubric (Reddy et al, 2019), whether observers are rigorously trained, and rating calibration is considered (Briggs & Alzen, 2019). Since data collected from observer ratings can possibly provide researchers with rich information about the actual teaching and learning process (Grossman et al, 2014; Hill et al, 2011; Pianta & Hamre, 2009), particularly when video recording of teachers’ lessons are obtained and then analyzed by trained raters, it has gained more popularity in recent decades with the affordance of modern video technology as evidenced by the Video Study of Trends in International Mathematics and Science Study (TIMSS) in the 1990s (Stigler & Hiebert, 2009) and then the Organization for Economic Co-Operation and Development (OECD)'s large scale Global Teaching Insights (GTI) study in 2018 (OECD, 2020a).…”
Section: Literature Reviewmentioning
confidence: 99%